Differences in shell morphology of the species Rochia nilotica (Linnaeus, 1767) and Rochia maxima (F. C. L. Koch, 1844) (Gastropoda: Tegulidae) - Bunjamin Dharma; Delianis Pringgenies (Masyarakat Moluska Indonesia, 2023)
Rochia nilotica (Linnaeus, 1767) previously known as Trochus niloticus Linnaeus, 1767, is known in Indonesia by the local name “lola” or “lolak”. In Indonesian waters, “lola” is easily and widely found, its shiny shell has a high selling value and is an industrial commodity with an export orientation. The other most similar species is Trochus maximus F. C. L. Koch, 1844. In adult shells, T. niloticus and T. maximus are easily distinguished by the shape of their shells; but their juvenile and semi-adult shells are easily confused with one another. Both species have large shells, 110-120 mm in diameter and 115-140 mm in height. Initially, these two species were included in the genus Trochus Linnaeus, 1758 of the family Trochidae Rafinesque, 1815. Bouchet & Rocroi, 2005 in the “Taxonomy of the Gastropoda“ approved the validity of the family Tegulidae Kuroda, Habe, & Oyama, 1971 of the superfamily Trochoidea Rafinesque, 1815, separate from the family Trochidae Rafinesque, 1815. These two large species are included in the genus Rochia Gray, 1857 from the family Tegulidae, becoming Rochia nilotica (Linnaeus, 1767) and Rochia maxima (F. C. L. Koch, 1844). Included in the family Tegulidae, among which are the genera Rochia Gray, 1857; Tectus Montfort, 1810; and Tegula Lesson, 1833. This paper discusses the differences between the two species Rochia nilotica (Linnaeus, 1767) and Rochia maxima (F. C. L. Koch, 1844) in terms of shell morphology. KEYWORDS: Tegulidae, Rochia, nilotica, maxima